A rheological approach to studying process-induced structural evolution of the microporous layer in a proton exchange membrane fuel cell. (1st September 2021) - Mehrazi, Shirin; Sarker, Mrittunjoy; Mojica, Felipe; Rolfe, Philip; Chuang, Po-Ya Abel
Highlights: Comprehensive study of solid content and PTFE loading in a microporous layer. Rheological investigation of MPL ink to study coating induced structural evolution. Discover the effect of MPL on dry and wet transport resistance and fuel cell performance. Graphical abstract: Abstract: Dispersions of carbon black and polytetrafluoroethylene (PTFE) are precursors of the microporous layer, which serve as a component of the gas diffusion media in a proton exchange membrane fuel cell. To optimize the function of the microporous layer, it is essential to develop a fundamental understanding of its microstructure, which depends on the ink formulation and coating shear forces. Here, the relationship between the primary agglomerate structure in the ink and the morphological and surface properties of the dried layer is studied based on the rheological properties. The ink formulation variables in this study are the solid content (5, 10 and 15 wt.%) and the PTFE loading (15, 25 and 35 wt.%). The results indicate that samples with higher PTFE loading have a more inhomogeneous microstructure and form highly percolated agglomerates after coating. Most of the bulk flow properties of the inks are dominated by the carbon mass fraction and exhibit a power-law relationship as a function of the carbon mass fraction. The microporous layer with a solid content of 10 wt.% and a PTFE loading of 25 wt.% is found to have an optimal morphology for oxygen transport under both dry and wet conditions due to the fact that it is not overly flocculated and has a wide distribution of carbon agglomerates sizes. The findings from this study provide new insight into the optimization of microporous layer design and development.